Teaching towards green schools transforming K-12 education through sustainable practices - Plevyak, Linda H. (New York, NY : Routledge, 2022)
This engaging and timely book showcases practical ways that PreK-12 teachers and school leaders can create and implement sustainability-focused projects and practices in their classrooms and schools, helping promote a healthy, sustainable environment and curriculum for students and leading the way towards becoming a green school. Sharing real-world case studies and detailed walk-throughs of sustainable schools in action - from Madison, Alabama, to Bali, Indonesia - author Linda H. Plevyak lays out the benefits, principles and practices of creating a sustainable school from beginner classroom projects like creating a garden, recycling and composting to more complex and school-wide initiatives like energy audits, creating an environmental management system, engaging with policy and building and leveraging community partnerships. Plevyak highlights sustainable practices that can be developed with little to no budget and focuses on those that support the development of critical thinking skills, promote project-based learning and consider the environment as a learning tool, incorporating sustainability as a natural progression of the learning process. The book outlines extensive resources teachers and schools can use to embed sustainability in their programs and curriculum, offering teachers, school leaders and policy makers the tools they need to provide this generation of students with the knowledge and skills to create a more sustainable world.
Keywords: EDUCATION / Teaching Methods & Materials / Science & Technology; EDUCATION / Leadership; Environmental education -- United States; Sustainability -- Study and teaching -- United States; Schools -- Environmental aspects -- United States; School improvement programs -- United States; School management and organization -- United States